Interpretation of Predicative Non-Assertive Relations in Structure of Utterance in Discourse of Russian Orthodox Sermon - V. A. Burtsev (Научный диалог, 2021)
The categorical affiliation and semantic characteristics of propositions that do not have the status of assertions in the current utterance are considered. Such propositions are denoted by the term “pre-conservative”. It is shown that the preassertive status of propositions is determined by two main factors: the grammatical factor of precedence / following of explicit or implicit predication with respect to the moment of speech and the discourse factor of presentation in the proposition of the preassertive information reflecting religious mentality and religious ideology. The action of these factors gives rise to the phenomenon of asubjectivation. With asubjectivization, the semantic content of a linguistic expression is determined only by the properties of the described situation, and not by the locutionary activity of the subject of speech. It has been established that whole sentences, including those with non-propositional meanings, can receive the “pre-passive” status. It is shown that, in terms of some properties, the preassertive is comparable to a number of units of different articulations of the semantic-syntactic structure of an utterance, however, its specific manifestation in connection with asubjectivation proves that this is a special category in relation to explicit predication. The research was carried out on the basis of the material of the Russian Orthodox sermon. The novelty of the research consists in the characterization of the preassertive as a new syntactic relation on the axis “assertion — non-assertive component” of the utterance. Relevance is determined by the fact that the work develops a fundamentally new aspect of the study of subjectivity in language.